How does climate exacerbate root causes of conflict in Kenya? An econometric analysis - Belli, Anna; Villa, Victor; Läderach, Peter R.D.; Pacillo, Grazia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This factsheet assesses how climate exacerbates root causes of conflict in Kenya, using a two-stage econometric approach. The findings show how rising temperatures and decreasing rainfall can have a significant impact on Kenyan households' nutrition security and that the interaction of climate and nutrition insecurity increases the intensity of conflict.